Predicted mechanical performance of pultruded FRP material under severe temperature duress - Ghadimi, Behzad; Russo, S.; Rosano, M. (Elsevier Ltd, 2017)
Pultruded FRP (fibre reinforced polymer) materials have attracted the attention of civil engineers with their high strength weight ratio and environmentally friendly production and use. Mechanical analysis of pultruded FRP profiles is complex since the material is anisotropic and becomes more complex when thin FRP dedicated hollow cross sections are involved. This is particularly relevant with square or rectangular construction forms where the corners of the material are suspected to produce weak points under compressive loading. FRPs are also believed to behave contrarily when subjected to heat and thermal duress. This research investigates problems in predicting their behaviour under compression (hollow square pultruded FRP sample) using different analytical and modelling approaches. The mechanical behaviour of the material is investigated under different thermal conditions through finite element simulation and the results are then compared with previously conducted laboratory research analysis. The large deformation in anisotropic materials is simulated to provide better prediction regarding the failure mechanism of this material. Finite element simulation is then used to estimate the performance of similar and often competitive construction materials to GFRP (i.e.: wood, concrete and steel) under similar thermal and compressive duress.